EFFECT OF VARIED RESISTANCE TRAINING ON PHYSICAL FITNESS AND SKILL RELATED VARIABLES OF SCHOOL BASKETBALL PLAYERS - N, Girisha; Rajan, Dr. A. Kaleb; M.G, Muniraju (The journal of contemporary issues in business and government, 2022)
Basketball is a popular team sport and physical fitness along with strategic game play is the key aspects of this game. Here in this concern article aim is to have an investigation of various effect of resistance training for skills and fitness development of School players in basketball. There several kinds of free hand exercises are involved in resistance training such as Deadlifts, Push Presses, push press, Bench Press, Squats, Rows, running etc. This concern resistance-based Exercise increases the skills of shooting, dribbling, defending, rebounding, and passing in the game of Basketball. Resistance training has helped a player to gain acrobatic ability, speed, and endurance. In schools ground and basketball court an school play usually add resistance for practices, these resistance training Is resistance training good for basketball movements. Player jump developed physical ability to jump higher, build strength, dribble down the court faster, and get on defence quicker and to be a highly trained, all-around better player.